Self-Assembled H-Bonding Superstructures for Alkali Cation and Proton Transport - Licsandru, Erol; Andrei, Iuliana-Marilena; van der Lee, Arie; Barboiu, Mihail (Frontiers in Chemistry, 2021)
Transmembrane protein channels are of significant importance for the design of biomimetic artificial ion channels. Regarding the transport principles, they may be constructed from amphiphilic compounds undergoing self-assembly that synergistically generate directional superstructures across bilayer membranes. Particularly interesting, these alignments may impose an artificial pore structure that may control the ionic conduction and translocate water and ions sharing one pathway across the cell membrane. Herein, we report that the imidazole and 3-amino-triazole amphiphiles self-assemble via multiple H-bonding to form stable artificial networks within lipid bilayers. The alignment of supramolecular assemblies influences the conduction of ions, envisioned to diffuse along the hydrophilic pathways. Compounds 1-8 present subtle variations on the ion transport activities, depending the structure of hydrophilic head and hydrophobic components. Fluorinated compounds 3, 4 and 7, 8 outperform the corresponding non-fluorinated counterparts 1, 2 and 5, 6. Under the same conditions, the R enantiomers present a higher activity versus the S enantiomers. The present systems associating supramolecular self-assembly with ion-transport behaviors may represent very promising unexplored alternatives for ion-transport along with their transient superstructures within bilayer membranes, paralleling to that of biology.